Advances on transition metal oxides catalysts for formaldehyde oxidation: A review. Issue 3 (3rd July 2017) - Yusuf, Abubakar; Snape, Colin; He, Jun; Xu, Honghui; Liu, Chaojie; Zhao, Ming; Chen, George Zheng; Tang, Bencan; Wang, Chengjun; Wang, Jiawei; Behera, Sailesh N.
ABSTRACT: This article highlights recent advances in the development of transition metal-based catalysts for formaldehyde oxidation, particularly the enhancement of their catalytic activity for low-temperature oxidation. Various factors that enhance low-temperature activity are reviewed, such as morphology and tunnel structures, synthesis methods, specific surface area, amount and type of active surface oxygen species, oxidation state, and density of active sites are discussed. In addition, catalyst immobilization for practical air purification, reaction mechanism of formaldehyde oxidation, and the reaction parameters affecting the overall efficiency of the reaction are also reviewed.